Effect of synthesis route on structure and properties of AlCoCrFeNi high-entropy alloy. (April 2017) - Uporov, S.; Bykov, V.; Pryanichnikov, S.; Shubin, A.; Uporova, N.
Abstract: A series of equatomic AlCoCrFeNi alloys prepared through various synthesis techniques is systematically investigated in the temperature range from 4 K to 1400 K. In this paper we consider their crystalline structure, microstructure, thermo-physical, electron-transport and magnetic properties. Phase transformations, Curie point and also the region for σ-phase existence are accurately determined in the system. A mixture of both body centered cubic (BCC) and face centered cubic (FCC) crystal structures is identified in all samples. Depending on synthesis conditions, BCC or FCC solid solution dominates that induces large variations in the properties of the alloys. Highlights: HEA AlCoCrFeNi is systematically investigated in a wide temperature range. All phase transformations in the system are accurately determined. Depending on synthesis route, BCC or FCC phase is dominated in the samples structure. The samples synthesized by different ways exhibit huge variations in their the properties.